ETHNO CULTURAL HERITAGE CARVED IN THE ART OF TENYIMIA KHARU - Sorhie, Petekhrienuo (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Strong traditional elements and ethnic culture comes to life and is made apparent in the crafts, art and practices of its people. Kharu which is a word spoken by the Tenyimia Nagas means ‘Village Gate’. Kharu is not a mere gate but it is a prodigious representation of rich cultural antiquity of the Tenyimia Nagas. The utilitarian aspect of it defines the traditional system of polity, defence mechanism, protection and sovereignty of most of Naga villages. The interest of this paper lies in showcasing and ruminate over the meaning, significance of traditional gates with varied motifs carved on it. The functional as well as the symbolical aspects of the Angami village gate is explicated along with the depiction of various art motifs on it. The paper will etch deep into the carvings of the Angami village gate and give a voice to the art that talks about a people who once upon a time lived in the sublimity of animism. However, the writing also delved into the transitioning times of the Nagas which is having its impact on the pristine nature of traditional practices. The author pens the paper with a concern to record the celebrated Kharu which stands replete with ethno-historical evidences rendering a voice of the past to the present.